Postoperative Adjuvant Radiotherapy Can Delay the Recurrence of Desmoid Tumors After R0 Resection in Certain Subgroups - Yang, Tielong; Liu, Haotian; Liao, Zhichao; Zhang, Chao; Xiang, Lijie; Yang, Jilong (Frontiers in Surgery, 2021)
Background: When patients with desmoid tumors (DTs) present uncontrolled clinical symptoms, surgery is an effective treatment, but the high postoperative recurrence rate is a major problem. The significance of adjuvant radiotherapy has been debated for many years, and the significance of aggressive surgery has not been reported. Methods: Medical records for DT patients were collected. KM analysis and the Mann-Whitney U test were performed to evaluate the role of radiotherapy and aggressive surgery in the entire cohort and different subgroups. Results: Of 385 DT patients, 267 patients with R0 resection were included in the final analysis. A total of 53 patients (19.85%) experienced recurrence. Although radiotherapy showed no significant effect on recurrence-free survival (RFS) or time to recurrence (TTR) in the entire cohort, radiotherapy delayed recurrence in the age <= 30 years old subgroup (TTR=35 months with surgery plus radiotherapy, TTR=11 months with surgery alone; p=0.014) and the tumor diameter > 5 cm subgroup (TTR=26 months with surgery plus radiotherapy, TTR=11 months with surgery alone; p=0.02) among patients with a single tumor. Aggressive surgery improved RFS in the tumor diameter > 5 cm subgroup (p=0.049) but not the entire cohort. Conclusions: Although radiotherapy cannot improve RFS, it can delay recurrence in the age <= 30 years old subgroup and the tumor diameter > 5 cm subgroup among patients with a single tumor. For patients with large invasive tumors and multiple involved sites, aggressive surgery could be selected to achieve complete tumor resection to improve RFS.